Atributos físicos e hídricos em argissolo vermelho amarelo sob diferentes usos na bacia do Rio Poxim - Batista, Lucas dos Santos (2017)
The watersheds are units of planning and environmental management with a great importance in water resource management and its use. To this end, the knowledge about the physical and hydric soil is of utmost importance in the context of the dynamics of water in areas of recharge of aquifers. The determination of the speed of water infiltration into the soil, hydraulic conductivity, soil moisture and soil mechanical resistance to penetration allow reconcile conditions of soil aggregation for each use, favoring greater water infiltration into the soil, which is considered a key piece in the hydrological cycle, because the increase of this process can lead to a reduction in soil erosion and consequently greater recharge of groundwater. The present study aimed to evaluate the physical attributes and water resources present in the phytophysiognomy of watershed of Poxim river in the Sergipe State, through the use of cylinder infiltrometer for determination of the infiltration rate and hydraulic conductivity and, also, the soil mechanical resistance to penetration with the aid of mobile penetrometer in the areas of agriculture, eucalyptus and native forest. The infiltration rate was estimated by means of mathematical models of Kostiakov, Kostiakov-Lewis, Horton and Philip. When comparisons are made between the models of estimates of speeds of infiltration, the model Horton showed a better adequacy in comparison to other models used, and the type of soil cover which had the highest rate of infiltration was the native forest. As for the hydraulic conductivity, there was no significant difference (p>0,05) for the different types of soil. In the soil, the mechanical resistance values to penetration were classified as moderate to extremely high.